2002
DOI: 10.1590/s0004-282x2002000400011
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of the lateral posterior and anteroventral thalamic nuclei on spontaneous recurrent seizures in the pilocarpine model of epilepsy

Abstract: -The pilocarpine model of epilepsy in rats is characterised by the occurrence of spontaneous seizures (SRSs) during the chronic period that recur 2-3 times per week during the whole animal life. In a previous study on brain metabolism during the chronic period of the pilocarpine model it was possible to observe that, among several brain structures, the lateral posterior thalamic nuclei (LP) showed a strikingly increased metabolism. Some evidences suggest that the LP can participate in an inhibitory control sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 11 publications
3
17
0
Order By: Relevance
“…Indeed, we found that over 46% of the CTZ rats (6 out of 13) had recurrent seizure with the latency between 2 weeks to 6 months. The silent period between acute seizure induction and the occurrence of the recurrent seizure in this CTZ seizure rat model seems well in agreement with the other classic seizure animal model, at around two-week time of latency, such as pilocarpine and Kainic acid induced seizure models [24, 25]. However, the rate of the animal to have recurrent seizure seems lower than other seizure models.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Indeed, we found that over 46% of the CTZ rats (6 out of 13) had recurrent seizure with the latency between 2 weeks to 6 months. The silent period between acute seizure induction and the occurrence of the recurrent seizure in this CTZ seizure rat model seems well in agreement with the other classic seizure animal model, at around two-week time of latency, such as pilocarpine and Kainic acid induced seizure models [24, 25]. However, the rate of the animal to have recurrent seizure seems lower than other seizure models.…”
Section: Discussionsupporting
confidence: 85%
“…Although we have demonstrated that CTZ induced seizure in freely moving rats [12], a successful seizure animal model requires the animals to develop recurrent seizure and also have a high proportion to have recurrent seizure [24]. In this aspect we carried out the current study to investigate whether the acutely induced seizure rats by CTZ could develop to have recurrent seizure.…”
Section: Discussionmentioning
confidence: 99%
“…As our AN lesions compromised a large volume of tissue (most of anteroventral thalamic nucleus and parts of the anterodorsal and anteromedial nuclei), they have likely also injured fibers from the mammillothalamic tract and efferents from the AN to the cingulum. Similar to our results however, Scorza et al [22] using chemical ablation with ibotenic acid (supposedly harmful only to neurons), have shown that lesions in parts of the anteroventral nucleus did not alter the frequency of spontaneous seizures in pilocarpine epileptic rats. Results from our study and the one by Scorza et al suggest that, independent on the extent of the lesion or the method used for their production, AN thalamotomies are not protective against SRS in chronic pilocarpine epileptic rats.…”
Section: Discussionsupporting
confidence: 92%
“…Before these studies are undertaken, it is prudent for us to clarify our research background. In a previous study, our research group found that the thalamus plays an interesting and important role in the cerebral circuits of rats with epilepsy67,68. Interestingly, in studies of epilepsy, which is the most prevalent serious neurological condition worldwide, clinical data suggest that these patients are at a two- to threefold higher risk of dying prematurely than those without epilepsy.…”
Section: Thalamic Nuclear Abnormalities and Sudden Cardiac Death In Smentioning
confidence: 90%